Enterprise Lean Management and Optimization Policy under the Impact of COVID-19 - Mengqi , Wang (Journal of Innovative Studies, 2020)
Under the impact of COVID-19, many enterprises have the problems of capital, effectiveness, and production for which it is vital to solving the problems by the true implementation of lean management. This article will briefly discuss the difficulties and processing strategies of enterprises by the research on the problems of enterprises in lean management and their optimization policy under the impact of COVID-19.